DNA immobilization, delivery and cleavage on solid supports - Singh, Vikram; Zharnikov, Michael; Gulino, Antonino; Gupta, Tarkeshwar (Journal of materials chemistry, 2011)
Progress in bio-molecular chemistry, nanotechnology, and surface engineering resulted in the fabrication of nanoscale bio-systems with advanced functionalities. These systems and the related methodologies offer new perspectives for the development of novel bio-related diagnostic tools and gene and/or photodynamic therapy. A key issue in this context is the design and fabrication of “smart surfaces” able to immobilize functional biomolecules and DNA in particular, which can perform a certain function (e.g. hybridize with the target DNA strand) or be delivered or cleaved under the input of external stimuli (chemical, electrochemical, thermal, photochemical, etc.). This review addresses the above points dealing first with immobilization of DNA on various solid substrates using a bottom-up approach and describing later subsequent transport and/or cleavage of DNA using various routes.